A Method for Measuring Difference in Activity of Phenolic and Non- Phenolic Groups Through 2,2` Azino-Bis-(3-Ethyl-Benzothiazoline-6- Sulphonate) Radical Cation - Masood, Nusrat; Luqman, Suaib (Combinatorial Chemistry & High Throughput Screening, 2014)
A 2, 2`azino-bis-(3-ethyl-benzothiazoline-6-sulphonate) radical cation-based method was optimized in 96 well plates to evaluate the comparative scavenging potential of phenolic and non-phenolic group of molecules with respect to control. The interactions of these molecules with ABTS radical cation were quantified on the basis of their relative influence on the bleaching of a bluish-green color complex in a structure- and dose-dependent manner. Experimentally, the developed assay provided evidence that phenolic molecules are more reactive with ABTS radical than non-phenolic compounds because of their resonance and hyper-conjugation effects.
Keywords: 2